Effects of non-invasive brain stimulation combined with cognitive training on cognitive functions in older people with mild cognitive impairment: a systematic review with meta-analysis - Vásquez-Carrasco, Edgar; Jamett-Oliva, Pía; Quijada, Amanda; Hernandez-Martinez, Jordan; Branco, Braulio Henrique Magnani; Carmine-Peña, Eduardo; Sepúlveda, Paulina; Sandoval, Cristian; Valdés-Badilla, Pablo (Frontiers in Medicine, 2025)
BackgroundNon-invasive brain stimulation (NIBS) has emerged as a potential adjunct to cognitive training for enhancing cognitive performance in older peoples with mild cognitive impairment (MCI). This systematic review and meta-analysis aimed to evaluate the efficacy of combined NIBS and cognitive training on cognitive function in this population.MethodsA comprehensive literature search was conducted in PubMed, EBSCOhost, CINAHL Complete, Cochrane Library, ProQuest, Scopus, and Web of Science up to May 2025. The review followed PRISMA guidelines, and methodological quality was assessed using the Oxford Centre for Evidence-Based Medicine levels, the Cochrane Risk of Bias 2 tool (RoB 2) tool for risk of bias, and the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach for the certainty of evidence. The protocol was registered in PROSPERO (CRD42024563219). Studies were included if they assessed the effects of NIBS in combination with cognitive training on cognitive outcomes in older peoples with MCI.ResultsA total of 1,689 records were screened, and 10 studies met the inclusion criteria. The results indicated a moderate positive effect of the combined intervention on attention and processing speed as measured by the Trail-Making Test Part A (TMT-A; effect size = 0.54). Improvements were also observed in global cognition as assessed by the Montreal Cognitive Assessment (MoCA), though the results were not statistically significant (p > 0.05). No significant effects were found for the Trail-Making Test Part B (TMT-B), with effect sizes ranging from 0.05 to 0.52.ConclusionThe combination of NIBS and cognitive training appears to yield beneficial effects on specific cognitive domains, particularly attention and processing speed, in older people with MCI. These findings support the potential role of NIBS as an adjunctive intervention to cognitive training for enhancing cognitive function in this population. Further high-quality randomized controlled trials are warranted to confirm these effects.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024563219, identifier (CRD42024563219).